Gene therapy for viral infections - Arbuthnot, Patrick (Elsevier Press is an imprint of Elsevier, 2015)
Gene Therapy for Viral Infections provides a comprehensive review of the broader field of nucleic acid and its use in treating viral infections. The text bridges the gap between basic science and important clinical applications of the technology, providing a systematic, integrated review of the advances in nucleic acid-based antiviral drugs and the potential advantages of new technologies over current treatment options. Coverage begins with the fundamentals, exploring varying topics, including harnessing RNAi to silence viral gene expression, antiviral gene editing, viral gene therapy vec.